PHYSICOCHEMICAL, ISOTOPIC, SPECTRAL, AND MICROBIOLOGICAL ANALYSES OF WATER FROM GLACIER MAPPA, CHILEAN ANDES - Ignatov, Ignat; Valcheva, Nedyalka (Journal of the Chilean Chemical Society, 2023)
Described are the physicochemical and microbiological parameters of glacial water sourced of Glacier Mapa, Andes Mountains, Chile. The study is performed of isotopic composition in collaboration with Oleg Mosin. Glacier Mapa is located 55 km from the town of Los Andes in direction of Argentina. The water of the given source Glacier Mapa, Chile is characterized by microbiological indicators. Research is conducted for Coliforms, Escherichia coli, Enterococci and Clostridium perfringens. The pathogenic micro-organisms in the samples of the glacial water from the source mentioned above are determined by the methods according to Ordinance No. 9/2001, Official State Gazette, issue 30, and decree No. 178/23.07.2004 of Council of Ministers, Bulgaria about the quality of water, intended for drinking and household purposes. The parameters of the physicochemical composition include 18 indicators and are determined according to Ordinance No. 9/2001 (Protocol No. 12735/17.03.2016 of licensed laboratory Eurotest control, Sofia, Bulgaria). The physicochemical and microbiological parameters of glacier water Mapa, Chile, correspond to all controlling parameters and are in accordance with Ordinance No. 9/2001 (Official State Gazette, issue 30 about the quality of water, intended for drinking and household purposes). The natural waters consist 99.7 mol. % of H216O, which are formed by 1H and 16O atoms (Jouzel, 2003; Mosin, Ignatov, 2011). The remaining 0.3 mol.% is distributed in isotope varieties (isotopomers) of water molecules, whose deuterium atoms form 6 configurations – HD16O, HD17O, HD18O, D216O, D217O, D218O, as 3 configurations are formed by isotopes of oxygen – Н216O, Н217O, Н218O. Studies of International standard SMOW of isotopic shift for D were performed for D/H for water from Glacier Mapa, Chile. The results obtained of glacier water Mapa, Chile show a lower content of hydrogen and oxygen isotopes. It is not confirmed presence of pathogenic micro-organisms. The physicochemical indicators are typical for waters during the ice melting in glacier water (Ca2+ 6.0; Mg2+ 1.0; Na+ 5.0; K+ 0.38; HCО3- 73.8 /mg. L-1). Glacier water Mapa is soft with total mineralization – 100.1 mg.L-1. The water of Glacier Mapa is beneficial for the health according to the indicated physicochemical, microbiological and isotopic parameters.